Analysis of the Need for Increasing Professional Competence of Elementary School Teachers - Zainal Berlian (STAI Hubbulwathan Duri, 2022)
This study aimed to describe the need for increasing teacher professional competence in the Way Tuba District Elementary School. This study uses a quantitative descriptive method. The research population is 166 teachers, and the research sample is 30 teachers. The data was obtained using a field study with a non-test technique in the form of a questionnaire. The data collection instrument uses a Likert scale that has been tested and has met the validity and reliability requirements. Data analysis used interval and descriptive percentage formulas. The results of the study indicate that the need to increase mastery of the field of expertise is mastering the teaching materials in the school curriculum with a result of 54%; mastering the competency standards and basic competencies of the lessons taught by 74%; understanding the relationship of concepts related subjects by 67%, and apply scientific concepts in learning by 50%. The need to increase the mastery of the scientific method structure is mastering the research steps with 50% results and applying scientific concepts in daily life by 50%. The need to increase the ability to guide students to meet competency standards is to guide students in mastering material knowledge skills with a result of 57% and guiding students in achieving learning objectives by 50%.